The Influence of the Project-Based Learning (PjBL) Model on Student's Science Process Skills and Critical Thinking - Triah Wulandari; Ervan Johan Wicaksana; Evita Anggereini (Postgraduate, University of Mataram, 2024)
Applying the project-based learning model in learning can train and develop scientific attitudes and problem-solving skills so that students can increase creativity, innovation, and critical perspectives. This research aims to determine the effect of the project-based learning model on student's science process skills and critical thinking. The research subjects of class X Phase E. This research was quantitative research with a quasi-experimental research design with a non-randomized control-group pretest-posttest design. The instruments used are essay questions on science process skills and critical thinking. The test results were analyzed using Quade's rank analysis of covariance statistical test and the One Way Ancova test. The research results show that the average pretest-posttest score of experimental class students taught using the project-based learning model is higher than that of control class students taught using the problem-based learning (PBL) model. Hypothesis testing using Quade's rank analysis of Covariance and One Way Ancova tets informs that the use of the project-based (PjBL) model affects student's science process skills and critical thinking.